North Qinling Paleozoic granite associations and their variation in space and time: Implications for orogenic processes in the orogens of central China - Wang, Tao; Wang, XiaoXia; Tian, Wei; Zhang, ChengLi; Li, WuPing; Li, Shan (Science China. Earth sciences, 2009)
Integrated zircon U-Pb dating and whole rock geochemical analyses have been carried out for two typical S-and I-type granitoids in the north Qinling. Zircon dating by SIMS of the Piaochi S-type grani- toids yields an emplacement age of 495±6 Ma. The granitoids show whole-rock εNd(t)=-8.2--8.8, zircon εHf(t)=-6―-39. The Huichizi I-type granitoids have emplacement ages of 421±27 Ma and 434±7 Ma es- tablished by LA-ICP-MS and SIMS methods, respectively. Their whole-rock εNd(t)=-0.9-0.9 and zircon εHf(t)=-11-8.4. Combined with statistical analyses of 28 zircon ages of granitoid plutons collected from the literature, Paleozoic magmatism in the north Qinling can be divided into three stages. The first-stage magmatism (~505-470 Ma) mainly occurred in the east part of the north Qinling and has features of an I-type arc, associated with which are S-type granitoids such as Piaochi pluton. The early granitoids (~505-490 Ma) have close spatio-temporal relations to ultra-high-pressure (UHP) rocks, and thus are interpreted as an oceanic subduction system along a continental margin. The second-stage magmatism (~450-422 Ma) occured through the whole north Qinling, and is characterized by I-type granitoids represented by the Huichizi pluton. The magma is interpreted as partial melting of lower crust mixed by mantle-derived magma in a collisional setting with the uplift of terranes. The third-stage magmatism (~415-400 Ma) is dominated by I-type granitoids and only took place in the middle part of the north Qinling, and is regarded as a late-stage collision. The spatial and temporal variations of the Qinling Paleozoic magmatism reveal protracted subduction/collision. The subduction was initiated from the east part of the north Qinling, earlier than that in the Qilian-northern Qaidam, Kunlun, and northern Dabie regions. This demonstrates variations in time of subduction, accretion and collision of separate blocks or terranes in the orogenic systems in central China.